Controle PID convencional e GPC adaptativo aplicados em um robô manipulador planar - Ferreira, Gustavo de sá (2016)
The present work aims at the development and implementation of the adaptive generalized predictive controller (GPC) and the proportional integral proportional controller (PID) in a two-degree planar manipulator robot (2 GDL) composed of a rotational link and another prismatic. The rotational link has as structure an extensive branch of aluminum in profile U, having as actuator a motor-reducer of continuous current, and as sensing a potentiometer of ten turns, that acts like transducer of angular position. The prismatic link consists of a double acting pneumatic cylinder with a through rod fixed inside the rotational link, having as actuator a proportional electropneumatic valve of five paths and three positions and as sensing a potentiometric ruler that acts as a linear position transducer . The obtaining of the representative mathematical model of the robot will occur through the estimator of recursive least squares (MQR). We present experimental results of the estimated models and system responses under the action of the designed controllers.